Regions of allelic imbalance in the distal portion of chromosome 12q in gastric cancer. Issue 3 (1st June 2003) - Schneider, B G; Rha, S Y; Chung, H C; Bravo, J C; Mera, R; Torres, J C; Plaisance, K T; Schlegel, R; McBride, C M; Reveles, X T; Leach, R J
Abstract : Aims: To define regions of loss on the distal portion of chromosome 12q in gastric adenocarcinoma. Methods: Microsatellite analysis on chromosome 12 was performed on 19 human gastric cancer cell lines using 77 markers, 71 of which were within or distal to 12q21; some portions of this region showed extended regions of homozygosity (ERHs) in 10 of 19 gastric cancer cell lines. In addition, microdissected tumour cells from 76 primary gastric adenocarcinomas were examined using 13 markers of interest implicated by the cell line data; 70% of these showed allelic imbalance (AI) at one or more markers in or distal to 12q21. Results: Mapping ERHs in the cell lines and sites of AI in the tumours identified three regions that contain putative tumour suppressor genes: region A is located within 2.8 Mb between markers D12S1667 and D12S88; region B, within 1.9 Mb between markers D12S1607 and D12S78; and region C, in 0.74 Mb between markers D12S342 and D12S324. Fluorescence in situ hybridisation (FISH) analysis in two cell lines confirmed that two of the ERHs reflected deletions, not amplifications, of D12S81 in region A and D12S340 in region C. FISH analysis of marker D12S1075 within an ERH containing region B in one cell line showed neither amplification nor deletion. AI on 12q was not associated with prognosis, but was associated with ethnicity of the patient. Conclusions: These results identify regions on chromosome 12 that appear to contain tumour suppressor genes important in the development of gastric cancer.